Evaluation of Melatonin Secretion and Metabolism Exponents in Patients with Ulcerative and Lymphocytic Colitis - Cezary Chojnacki (Molecules, 2018)
Inflammatory bowel diseases, particularly ulcerative colitis (UC) and lymphocytic colitis (LC), affect many people. The role of melatonin in the pathogenesis of UC is precisely determined, whereas in LC it remains unknown. The aim of this study was to compare the expression of the melatonin-synthesizing enzymes tryptophan hydroxylase (TPH1), arylalkylamine-N-acetyltransferase (AANAT), and N-acetylserotonin methyltransferase (ASMT) in the colonic mucosa and urinary excretion of 6-sulfatoxymelatonin in patients with ulcerative and lymphocytic colitis. The study included 30 healthy subjects (group C), 30 patients with severe ulcerative colitis (group UC), and 30 patients with lymphocytic colitis (group LC). The diagnosis was based on endoscopic, histological, and laboratory examinations. Biopsy specimens were collected from right, transverse, and left parts of the colon. The levels of mRNA expression, TPH1, AANAT, and ASMT were estimated in the colonic mucosa with RT-PCR. The urine concentration of aMT6s was determined by the photometric method. The expression of TPH1, AANAT, and ASMT in colonic mucosa in UC and LC patients was significantly higher than in healthy subjects. Significant differences were found in the urinary aMT6s excretion: group C—13.4 ± 4.8 µg/24 h, group UC—7.8 ± 2.6 µg/24 h (p < 0.01), group LC—19.2 ± 6.1 µg/24 h (p < 0.01). Moreover, a negative correlation was found between fecal calprotectin and MT6s—in patients with UC − r = −0.888 and with LC − r = −0.658. These results indicate that patients with UC and those with LC may display high levels of melatonin-synthesizing enzymes in their colonic mucosa, which could possibly be related to increased melatonin synthesis as an adaptive antioxidant activity.